Designing Business Model Innovation for Sekolah Juara's Social Enterprise Sustainability - Duzan Janitra, Atha; Gustomo, Aurik (Journal Integration of Social Studies and Business Development, 2026)
Indonesia's expansion of the 13-year compulsory education program has fundamentally altered the national educational landscape, reinforcing the state's role as the primary provider of basic education. This structural shift has presented unintended existential challenges for philanthropic schools like Sekolah Juara, which historically relied on donor funding to serve underprivileged communities. As public perception increasingly views education as a state responsibility, donor support has declined, leaving the organization at a strategic crossroads: facing rising financial constraints while operating a legacy donation-dependent model in an increasingly competitive environment. This study investigates how philanthropic schools can redesign their business models to achieve long-term financial sustainability without compromising their social missions. Employing a qualitative case study approach, the research draws on in-depth interviews, document analysis, and literature review to capture the strategic adaptations required in a post-donor context. The findings propose a Business Model Innovation (BMI) framework driven by four strategic imperatives: (1) the institutionalization of teaching quality, (2) excellence-based market positioning, (3) the development of quality-aligned revenue streams, and (4) the cultivation of a sustainable investment ecosystem. Theoretically, this study extends the BMI literature by highlighting the "capability-led" transformation required for educational social enterprises. Managerially, it offers a structured strategic pathway for non-profit leaders navigating the complex transition from donor dependency to organizational resilience.